Overview of Akatsuki data products: definition of data levels, method and accuracy of geometric correction - Kazunori Ogohara; Masahiro Takagi; Shin-ya Murakami; Takeshi Horinouchi; Manabu Yamada; Toru Kouyama; George L. Hashimoto; Takeshi Imamura; Yukio Yamamoto; Hiroki Kashimura; Naru Hirata; Naoki Sato; et al. (Earth, Planets and Space, 2017)
Abstract We provide an overview of data products from observations by the Japanese Venus Climate Orbiter, Akatsuki, and describe the definition and content of each data-processing level. Levels 1 and 2 consist of non-calibrated and calibrated radiance (or brightness temperature), respectively, as well as geometry information (e.g., illumination angles). Level 3 data are global-grid data in the regular longitude–latitude coordinate system, produced from the contents of Level 2. Non-negligible errors in navigational data and instrumental alignment can result in serious errors in the geometry calculations. Such errors cause mismapping of the data and lead to inconsistencies between radiances and illumination angles, along with errors in cloud-motion vectors. Thus, we carefully correct the boresight pointing of each camera by fitting an ellipse to the observed Venusian limb to provide improved longitude–latitude maps for Level 3 products, if possible. The accuracy of the pointing correction is also estimated statistically by simulating observed limb distributions. The results show that our algorithm successfully corrects instrumental pointing and will enable a variety of studies on the Venusian atmosphere using Akatsuki data.